2018
DOI: 10.1111/jmp.12332
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive congenital cataract in captive‐bred vervet monkeys (Chlorocebus aethiops)

Abstract: Although the three missense mutations in GCNT2 have a benign effect, a possibility exists that the candidate genes (GCNT2, HSF4 and CRYAA) might harbour mutations that are responsible for total congenital cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…As previously reported, only 8% of the vervet colony presented with total congenital cataract of which six families have been identified . Thus far, mutations in different congenital cataract genes have been reported from this colony . In the current study, seven of the eight novel sequence variants identified in the four screened genes were predicted to be disease‐causing.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…As previously reported, only 8% of the vervet colony presented with total congenital cataract of which six families have been identified . Thus far, mutations in different congenital cataract genes have been reported from this colony . In the current study, seven of the eight novel sequence variants identified in the four screened genes were predicted to be disease‐causing.…”
Section: Discussionsupporting
confidence: 61%
“…To further support the notion that the variants identified in this study may be responsible for cataract development within the aforementioned colony, a comprehensive summary was conducted between the current and previously reported study of which the same cataract animals were used. Both studies identified 23 sequence variants in seven genes ( CRYAA , HSF4 , GCNT2 , BFSP1 , CRYBB1 , GALK1 , and GJA8 ) of which eight were missense and 15 silent.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations